The emergence of projected scaled patterns of extreme temperatures over Europe - Ozturk, Tugba; Canbaz, Emine; Bilgin, Başak; Matte, Dominic; Kurnaz, M. Levent; Christensen, Jens Hesselbjerg (Frontiers in Earth Science, 2023)
This work investigates the scalability of extreme temperatures over the European domain with global warming levels. We have used the EURO-CORDEX ensemble of regional model simulations at 0.11° resolution for daily minimum and maximum temperatures to analyze future changes in extreme weather daily events. A scaling with the annual mean global warming modeled by the driving GCM is applied to future extreme temperature indices changes. The annual minimum of the lowest temperature of the day (TNn) increases more than the annual maximum of the highest temperature of the day (TXx) for Europe. The multi-model mean of the changes in scaled patterns of extreme temperatures arises very early, around 2020, even before it becomes robust. Individual scaled patterns of TNn and TXx emerge from around 2040.